Papulo-pustulosis form rosacea – results of immunohistochemical research of the condition of the lesions - Sviatenko T.V.; Haritonova E.G. (Морфологія, 2012)
Studying and the analysis of links pathogenesis papulo-pus tulosis forms of rosacea by means of a wide spectrum of immunohistochemical markers became a research problem. For the decision of tasks in view by the author it is used biopsy a material of 11 diagnosed cases papulo-pus tulosis forms of rosacea at me at the age from 32 till 59 years. Use of immunohis-tochemical methods of research has allowed to reveal new links in pathogenesis of rosacea and to establish a role of some cellular populations of a skin and cages of immune system in progressing of disease and development papulo-pustulosis forms of rosacea. Authors have come to a conclusion that is possible, strengthening of pathological changes at papulo-pustulosis forms of rosacea is caused by presence of pincers which are capable to cause migration in skin CD68+ cages while quantity CD138+ plasmocytes was insignificant and didn't exceed 5-10 % in infiltrates. К i-67+ cages in a considerable quan-tity were as a part of sebaceous glands that specified in progressing hyperplastic changes in these appendages of a skin. Be-sides, the quantity of cages, pos itive on this marker, correlated wi th expressiveness of defeat of sebaceous glands in a greate r degree, than with a disease stage.